Modification of eating habits and lifestyle during COVID-19 in university students from Mexico and Peru - Arispe-Alburqueque, Claudia Milagros; Díaz del Olmo-Morey, Fernando Luis; Arellano Sacramento, César; Sánchez-Mendoza, Benjamín Dario; López-González, Martha Patricia; Yangali-Vicente, Judith Soledad; Ipanaqué-Zapata, Miguel; Alvarez-Risco, Aldo; Del-Aguila-Arcentales, Shyla; Yáñez, Jaime A.; Alvarado-Santiago, Tania Ivette; Morales-Martínez, Marx Engels (Frontiers in Nutrition, 2024)
The main objective of the study was to evaluate changes in lifestyle habits and health behavior among university students in Peru and Mexico during periods of confinement associated with the COVID-19 pandemic, and to identify possible relationships between these changes and sociodemographic variables, health status, and technology consumption. It was a quantitative, observational, and cross-sectional study conducted among a population of 739 Mexican students and 305 Peruvian students, most of whom were women (n= 778, 74.5%), and non-graduates (n= 921, 88.2%). The questionnaire scale of changes in lifestyles during the quarantine period has been previously validated. The association between sociodemographic factors and dimensions of change in healthy lifestyles was evaluated, it was shown that gender and country of residence were significant for all dimensions of healthy lifestyle (p<0.05), except for the level educational, which did not show significance about the change in the dimensions of media consumption (p=0.875) and physical activity (p=0.239). Within the dimensions mentioned, it can be stated that women are more likely than men to change their eating habits (aPR=1.08, p<0.001), media consumption (aPR=1.04, p<0.001) and physical activity (aPR=1.02), p<0.001). Meanwhile, participants from Peru are more likely than participants from Mexico to change physical activity (aPR=1.14, p<0.001) and media consumption (aPR=1.22, p<0.001). Finally, graduate students were more likely than undergraduate students to change eating habits (aPR=1.09, p=0.005) and unhealthy habits (aPR=1.06, p=0.030). It was concluded that there were lifestyle changes in the Mexican and Peruvian university students in their eating habits, physical activity, internet consumption and food delivery.